Review Cerebral Ischemic Tolerance and Preconditioning: Methods, Mechanisms, Clinical Applications, and Challenges - Hao, Yulei; Xin, Meiying; Feng, Liangshu; Wang, Xinyu; Wang, Xu; Ma, Di; Feng, Jiachun (Frontiers in Neurology, 2020)
Stroke are among the leading causes of morbidity and mortality worldwide, and are increasing in prevalence. The narrow therapeutic window and potential side effects limit the clinical application of the venous injection of thrombolytic tissue plasminogen activator and thrombectomy, which are regarded as the only approved treatments for acute ischemic stroke. Triggered by various types of mild stressors or stimuli, ischemic preconditioning (IPreC) induces adaptive endogenous tolerance to ischemia/reperfusion (I/R) injury by activating a multitude of proteins, enzymes, receptors, transcription factors, and other biomolecules eventually leading to genomic reprogramming. During the past decades, IPreC has been widely studied to confirm its neuroprotection against subsequent I/R injury, including local ischemic preconditioning (LIPreC), remote ischemic preconditioning (RIPreC) and cross preconditioning. Although LIPreC has a strong neuroprotective effect, clinical application of IPreC for ischemic brain is diffcult because they cannot be predicted and are also capable of producing injury with only minor changes to intensity or durations. RIPreC and pharmacological preconditioning, an easy-to-use and noninvasive therapy, can be performed in various clinical scenarios and appear to be more clinically relevant for the management of ischemic stroke. This review focuses on recent advances in IPreC in stroke management, its challenges, and the potential study directions, with the hope of advancing our understanding of this promising neuroprotective strategy for ischemic stroke in the near future.